DETERMINAN PENDAPATAN USAHATANI PADI SAWAH IRIGASI MENGGUNAKAN UNIT OUTPUT PRICE COBB DOUGLAS PROFIT FUNCTION DI KABUPATEN BANYUMAS - Ulfah Nurdiani; Rifki Andi Novia; Altri Mulyani (Universitas Galuh, 2023)
This study aimed to examine the determinants of income for irrigated rice farming in Banyumas Regency. This research was used analytical descriptive method with the survey method for the technical implementation. Determination of the research location used purposive method, considering that the majority of the research locations were technically irrigated rice fields. Determination of irrigated rice farming income in Banyumas Regency used the Cobb-Douglass type UOP profit function (Unit Output Price of Cobb-Douglass Profit Function). The results showed that the income of irrigated rice farming in Banyumas Regency was negatively affected by the price of Urea fertilizer and the price of pesticide, and positively influenced by the area of land used for irrigated rice farming. Meanwhile, the price of seeds, Phonska & TSP fertilizer prices, labor wages, and depreciation of the equipment used did not significantly affect the income of irrigated rice farming in Banyumas Regency.